Training on Making Biopesticide Made from Daun Belimbing Wuluh at the Women's Farming Group “Nanas Madu” in Buket Meutuah Village, Langsa City - Boy Riza Juanda; Iswahyudi; Iwan Saputra (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2023)
The majority of farmers in Indonesia still use chemical pesticides to treat pests and diseases in the commodities they grow. One of the plants that can be used as an environmentally friendly alternative to biopesticides is starfruit leaves. The large availability and ease of obtaining starfruit leaves, especially in Aceh in general and in Langsa City in particular, makes it potential to be used as a biopesticide which can be used by farmers in Langsa City, especially vegetable farmers. The farmer group that is a partner in this service activity is the "Nanas Madu" Farming Women's Group (KWT). KWT “Nanas Madu”. Based on field surveys conducted, it was revealed that not many farmers are aware of the dangers posed by the use of chemical pesticides over a long period of time. They also don't know about the existence of biological pesticides which are much cheaper and less dangerous and the manufacturing process is very easy. In Buket Meutuah village there are no effective and environmentally friendly control alternatives available, so farmers are very dependent and rely on chemical pesticides to control pests and plant diseases. This is due to the low level of knowledge of human resources among vegetable farmers and the lack of technology for the propagation and manufacture of biopesticides made from biological materials that are safe, effective and environmentally friendly.